O imperativo da reforma política - Lamounier, Bolívar (Revista USP, 2022)
The reform of political institutions is a constant theme in the history of independent Brazil. After more than three quarters of a century since the Second World War, there is no doubt that the Brazilian impasses have reached an astonishing dimension and that we will not be able to overcome them without a comprehensive and energetic political reform.